Sistem Pengambilan Keputusan Penerimaan Pegawai Kontrak Menggunakan Metode SAW pada Dinas Syariat Islam Provinsi Aceh - Iqbal, Saifuddin (Journal Digital Technology Trend, 2024)
The recruitment process for contract employees in government institutions often encounters obstacles due to its reliance on manual procedures, which are prone to errors, time-consuming, and influenced by subjectivity. This study develops a web-based Decision Support System to support the selection process at the Aceh Islamic Sharia Office by applying the Simple Additive Weighting (SAW) method. The research employed the waterfall approach, which included requirements analysis, system design, implementation, and testing. The system was developed using PHP and MySQL as its core technologies. The results indicate that the SAW method provides more objective and measurable rankings of applicants compared to manual procedures. The system also generates transparent reports, accelerates the selection process, and reduces human error. Therefore, the application of SAW is proven to be effective in supporting a fairer and more efficient recruitment process within government institutions.